Enhanced strength and wear resistance of a titanium-oxygen alloy with core-shell network structure. (July 2017) - Zhang, Y.S.; Han, Z.; Wang, X.; Zhang, W.; Huo, W.T.
Abstract: An enhanced sliding wear resistance of a novel core-shell Ti-O (CS-TiO) structured alloy combined with superior compressive properties relative to a commercial pure Ti (CP-Ti) compact is reported. The wear volume, area fraction of transfer layer in the contact zone and O content on the worn scars ( O at% ) were determined under various conditions. For CS-TiO, the prominent enhancement in wear resistance by more than 2 times is related to the increased O at% and improved yield strength, from 420 MPa in CP-Ti to 1210 MPa, which can effectively prevent it from experiencing serious adhesion and plastic deformation respectively. The study opens a new sight for microstructural design of anti-wear Ti alloys and composites: promoting tribo-oxidation reaction as well as improving strength. Highlights: A novel core-shell network structural Ti-O alloy has been fabricated successfully. Improved compressive properties and wear resistance have been achieved. Wear resistance is related to enhanced O content on worn scars and strength.